1955
DOI: 10.1136/hrt.17.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Age and Sex Factors in Coronary Artery Disease

Abstract: Age and sex have hitherto received less consideration than they merit in publications dealing with prognosis and mortality in coronary artery disease. Yet a clear knowledge of all factors that influence mortality is of paramount importance at a time when the efficicacy of modern methods of treatment is under critical review. Even in the matter of their influence on etiology, age and sex have received less prominence than the facts would seem to justify.It is common knowledge that coronary artery disease is muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1957
1957
1991
1991

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…1 Since then age has been incorporated into several "prognostic indices"2-5 yet papers continue to appear which claim very low hospital fatality rates for patients with myocardial infarction with little or no mention of the age of the population studied. 6 7 In this paper we re-emphasise the extreme importance of the patients' ages in any study of the outcome of myocardial infarction.…”
mentioning
confidence: 99%
“…1 Since then age has been incorporated into several "prognostic indices"2-5 yet papers continue to appear which claim very low hospital fatality rates for patients with myocardial infarction with little or no mention of the age of the population studied. 6 7 In this paper we re-emphasise the extreme importance of the patients' ages in any study of the outcome of myocardial infarction.…”
mentioning
confidence: 99%
“…Analysis of the different statistics shows that the female in cidence of arteriosclerotic heart disease complicated by myo cardial infarction varies greatly from one country to the other. Many of the Anglo-Saxon (11,12,16,43,47,48) and Scandinavian (42) authors report a male to female ratio lower than the ratio found by many Italian investigators (5. 6, 9, 13).…”
mentioning
confidence: 73%
“…According to some authors (5, 10, 33), the prognosis of myocardial infarction is more severe for women than for men, according to others (15) it is more severe for men than for women. Fitzgerald Peel (16), on the other hand, gives figures which seem to indicate that the death rate from infarction in the two sexes is very different in young age: up to the age of 55 years, the death rale is 6.8 per cent for men and 23.5 per cent for women; after that age, it increases to 35 and 28 per cent, respectively.…”
mentioning
confidence: 99%
“…However, we found gross coronary atheroma in 69 %0. In the young, males are much more often affected by coronary heart disease than females, though this is much less apparent by the eighth decade (Peel, 1955). Peel also found that the expectation of life in those with coronary heart disease diminished rapidly after the age of 55.…”
Section: Discussionmentioning
confidence: 99%